Intellectuals, Ideology and Football (8gen-ART, 2024)
Football is the most popular sport today, with ancient origins. This is why various countries have tried to trace its origins back to their own history. Initially, governments and intellectuals tended to ignore football. This was because of its violent nature, its potential power and its connotation of war. Later on, football became too important an industry to be ignored. Parallel to this, governments have tried to take advantage of football's ability to canalize the masses. Social scientists and intellectuals have also become more interested in football. Ideology-based definitions of football are valid for the ancient times of modern football. On the other hand, with the transformation of football into an ideology in itself, religious, class-based or ideological approaches have largely lost their meaning. In this study, this ideological transformation of football will be discussed.
Keywords: Football; Ideology; Class; Power